'But we can't call 911': undocumented immigrant farmworkers and access to social protection in New York. (2nd January 2017) - Sexsmith, Kathleen
Abstract: This paper analyzes access to healthcare for undocumented Mexican and Central American immigrant farmworkers who live and work in New York dairies. It assesses the regulatory framework – the conjuncture of immigration, employment, and occupational safety and health laws – which results in workers' exposure to workplace safety and health risks. It also analyzes their healthcare resource environments, meaning whether and how they gain access to medical services from actors in the public, private, third-party, and informal sectors. The paper finds that there exist significant gaps and contingencies in undocumented dairy farmworkers' resource environments, and that informal networks largely shape their access to the limited available public and third-party healthcare services available. Findings are based on 43 semi-structured interviews with undocumented dairy farmworkers and participant observation on farms.